ANALISIS PENGUKURAN TINGKAT KEMATANGAN SISTEM INFORMASI AKADEMIK MENGGUNAKAN COBIT 5.0 DI POLITEKNIK X - Mecca Sufyana, Candra; Suharto, Edi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2018)
The research objective was to evaluate and determine how far the application of information system academic that are running (including management controls and application controls) have been able to provide reliable information and where time and reduce risk to an acceptable level by the Polytechnic also provides recommendations for Polytechnic in order to minimize the risk that existed at themoment. This research describes the IT governance maturity level analysis of the Polytechnic X Academic Information System using COBIT 5.0 framework. This research will find the value of the IT governance maturity level current conditions of STMIK Lombok’s Academic Information System management. This maturity level value as a measure of the alignment of the implementation of the Academic Information System to Improve customer orientation and service and Services. Base on the maturity level average calculation results of Implementation the Polytechnic Academic Information System using DSS Domain are at level 3. The results of this study was to determine the academic of information system applications can provide adequate and reliable information and timely, thus simplifying the management to make sound decisions related to academic policy.